Um modelo consistente para o processo de fotocontagem contínua e medidas de emaranhamento de sistemas quânticos de variáveis contínuas - Dodonov, Alexandre (2005)
This dissertation embraces two trends of research in modern quantum optics. The first of them is connected to the photodetection theory, particularly to the continuous measurement theory developed by Srinivas and Davies (SD) in 1980 s, whose principal ingredient is the correct choice of the quantum jump superoperator. We deduce from first principles diﬀerent possible quantum jump superoperators, and employ one of them the nonlinear quantum jump superoperator, proposed independently ad hoc by Ben-Aryeh and Brif and Oliveira et al. to study the modifications it brings to the SD theory. We call this model as E-model and generalize the both models (SD model and E-model) by including dissipation eﬀects due to the imperfections of the cavity and of the detector. Finally, we study some specific applications of continuous photodetection theory (homodyne detection and detection of correlated photons) and compare the results between the two models. The second trend of this dissertation is related to the study of entanglement of continuous variables quantum states. We give a simplified form of Simon s separability criterion for two-mode Gaussian states, showing that for systems whose unitary evolution is governed by arbitrary time-dependent quadratic Hamiltonians, the separability dynamics is completely described in terms of the determinant of the cross-covariance matrix. As concrete examples we consider the evolution of the inverse negativity coeﬃcient (which gives a quantitative estimation of the degree of entanglement ) for two initially uncoupled modes (each being in a squeezed thermal state) in the cases of parametric converter, parametric amplifier and for a cavity whose boundary oscillates in resonance with two field modes.